Online buyer behaviour : a literature review. - Chong, Irene. (2008)
With an emerging growth in e-commerce activities, there has been a resurgence of research work in the field of online buyer behaviour in recent years. Our goal is to (1) explore online consumer navigation behaviour, specifically how do they retrieve and process information in online environments and (2) examine which determinants influence online search behaviour.